Otimização e validação de metodologia para determinação multirresíduos de agrotóxicos em alface e solo empregando QuEChERS e LC-MS/MS - Rego, Teresa Cristina Epifânio Diógenes (2015)
The use of pesticides in the class of organophosphates and carbamates from the 1940s and 1950s in Brazil brought benefits in combating pests on food crops, but also caused negative impacts to human health and the environment due to the presence of these compounds in food, water and soil. Therefore, it is essential to develop analytical methods for Multiresidue determination of pesticides in food and environmental matrices. This work is optimized and validated an analytical methodology for the determination of pesticides in the class of carbamates (carbaryl and carbofuran), organophosphates (chlorpyrifos, dimethoate, malathion and methamidophos) and neonicotinoid acetamiprid in samples of lettuce and ground using QuEChERS and reverse-phase liquid chromatography coupled to mass spectrometry with electrospray ionization (ESI-LC/MS/MS) operated in Mode Reaction Monitoring Multiple (MRM); the sample preparation QuEChERS method originally developed for food analysis, this work has been optimized both in the analysis of samples of lettuce, as well as in soil samples, seeking a fast, practical and efficient preparation of environmental samples. To meet the proposed objectives, additions of the seven pesticides at the level of fortification 5.0 μg kg-1 in samples of lettuce and soil were made, obtaining recoveries between 67.8 to 102.7% in lettuce, and between 73-121.1% in soil, with repeatability and intermediate precision with coefficients of variation below 15% for both matrices and quantitation limit of 1.0 μg kg-1 for seven pesticides; the effect matrix in selected samples was circumvented by diluting the extracts. To verify the applicability of the optimized and validated method were collected samples of lettuce and soil directly from producers, none of the seven pesticides standards researched found; as this study was conducted in a vegetable producing community than conventional cultivation, or with pesticides, it has been converted to organic production, the fact that no quantification of the compounds studied confirms the discontinuance of the use of these substances by selected farmers.